2014
DOI: 10.7314/apjcp.2014.15.16.6525
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Breast Self-Examination among Female University Nursing Students in Turkey

Abstract: Asian Pac J Cancer Prev, 15 (16), 6525-6529 IntroductionBreast cancer is currently the most prevalent cancer among women in both the developed and developing countries (WHO, 2014). In 2012, 1.7 million women were diagnosed with breast cancer. There were also 6.3 million breast cancer survivors who had been diagnosed with the disease in the previous five years. Breast cancer is also the most common cause of cancer death among women (522,000 deaths in 2012) and the most frequently diagnosed cancer among women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 17 publications
6
35
1
6
Order By: Relevance
“…In this study we think that the fact that the majority of the nursing students have performed BSE result from various factors such as they know how to do it, fear of having a cancerous mass, there are relatives who suffer breast cancer, they are conscious of the BSE benefits and aware of the effectiveness of BSE. The results of the studies that have been conducted in Turkey in the previous years show that the rate of women who have performed BSE is quite low (Findik and Turan, 2004;Gocgeldi et al, 2008;Ozgun et al, 2009;Erbil and Bolukbas, 2014;. Similar to the finding of this study, Alsaif (2004) has reported that the majority of nursing students had performed BSE.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study we think that the fact that the majority of the nursing students have performed BSE result from various factors such as they know how to do it, fear of having a cancerous mass, there are relatives who suffer breast cancer, they are conscious of the BSE benefits and aware of the effectiveness of BSE. The results of the studies that have been conducted in Turkey in the previous years show that the rate of women who have performed BSE is quite low (Findik and Turan, 2004;Gocgeldi et al, 2008;Ozgun et al, 2009;Erbil and Bolukbas, 2014;. Similar to the finding of this study, Alsaif (2004) has reported that the majority of nursing students had performed BSE.…”
Section: Discussionsupporting
confidence: 80%
“…For early detection of breast cancer; breast self examination every month after age 20, an annual mammogram after age 40, and 20-30's age 1-3 years in a clinical breast exam every year after the age of 40 is recommended by the American Cancer Society (Kara and Acikel, 2009;Erbil and Bolukbas, 2014;Khazee-Pool et al, 2014). However according to the various research studies the efforts directed at letting women develop a favorable attitude towards the early diagnosis of breast cancer have not been very adequate.…”
Section: Introductionmentioning
confidence: 99%
“…Educational programs have an important role to promote breast cancer screening behaviors and the health of women (Erbil and Bolukbas 2014). Stages of Change and Health Belief Models are the two most common models that have been applied for mammographic screening behaviors (Glanz et al, 2008;Hayden, 2009).…”
Section: Gulengul Mermer 1 * Meral Turkmentioning
confidence: 99%
“…In addition, cancer is an important cause of illness and mortality in Thailand and around the world (Duangsong et al, 2013;WHO, 2010). Prevention, caring, and recovery efforts depend on various family-and community-based interventions, theories and for these to be successful a participatory approach is necessary (Ahmadian and Samah, 2013;Al-Azri et al, 2014;Danawala et al, 2014;Erbil and Bolukbas, 2014;Jo et al, 2014;Lin et al, 2014;Sano et al, 2014;Sercekus et al, 2014;Simayi et al, 2013). However, realizing nursing and health caring that emphasizes family as a key focus of care within the family and community context can be a significant challenge for healthcare educators, practitioners RESEARCH ARTICLE…”
Section: Introductionmentioning
confidence: 99%